STUMP, a surprise finding in a large fibroid uterus in a 20-year-old woman - Hughes L; Roex A; Parange A (Dove Medical Press, 2018)
Lara Hughes, Alphonse Roex, Anupam Parange Obstetrics and Gynecology Department, The Lyell McEwin Hospital, Adelaide, SA, Australia Abstract: We report on a case of a 20-year-old nulliparous woman with menorrhagia associated with a smooth muscle tumor of uncertain malignant potential (STUMP) that was responsive to Goserelin. This case details the investigation and management of a young woman who desires ongoing fertility preservation. STUMP is a rare uterine tumor with a paucity of literature available regarding management and subsequent malignant potential, particularly in the case of a patient who desires fertility preservation. Keywords: smooth muscle tumor of uncertain malignant potential, STUMP, malignant potential, fertility preservation, fibroid uterus